Schyłek metafory. Rzecz o księdze Natury - Sierotowicz, Tadeusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The book of nature expressed both the possibility of knowing/reading of nature and the relationship between the experimental science and other books, mainly the book of Revelation. However, the role and significance of the metaphor changed with the development of natural science, and now the book of nature seems to obscure other books, and, moreover, its reading became the model of reading in general. Actually this metaphor is not a living metaphor any more, as it does not create, but closes and eclipses. Hence the need to look for a new one. This story is told here on the basis of Teodor Parnicki’s prose, who was a very careful observer and connoisseur of history of ideas, and of history as a mode of literature.